Balancing Open Science and Data Privacy in the Water Sciences - Zipper, Samuel C.; Stack Whitney, Kaitlin; Deines, Jillian M.; Befus, Kevin M.; Bhatia, Udit; Albers, Sam J.; Beecher, Janice; Brelsford, Christa; Garcia, Margaret; Gleeson, Tom; O'Donnell, Frances; Resnik, David; et al. (Water resources research, 2019)
Open science practices such as publishing data and code are transforming water science by enabling synthesis and enhancing reproducibility. However, as research increasingly bridges the physical and social science domains (e.g., socio‐hydrology), there is the potential for well‐meaning researchers to unintentionally violate the privacy and security of individuals or communities by sharing sensitive information. Here we identify the contexts in which privacy violations are most likely to occur, such as working with high‐resolution spatial data (e.g., from remote sensing), consumer data (e.g., from smart meters), and/or digital trace data (e.g., from social media). We also suggest practices for identifying and addressing privacy concerns at the individual, institutional, and disciplinary levels. We strongly advocate that the water science community continue moving toward open science and socio‐environmental research and that progress toward these goals be rooted in open and ethical data management. Key Points Natural scientists have little guidance to deal with privacy concerns for open science, which are inherent in socio‐environmental research Hydrology data with potential privacy concerns include high‐resolution spatial data, consumer data, and digital trace data Scientists should continue to share data openly while proactively addressing privacy concerns via ethical data management and sharing